Bulletin of the International federation of lithographers, printers and similar trades. . Bulletin of the International Federation of Lithographers, Lithographic Printers and kindred trades
Till no.74 text in Engl., French and German. - No.99-100 titled: Bulletin of the International Federation of Lithographers, Lithographic Printers and kindred trades. - French (ZK 16036), German ed. (ZK 16034).